A novel octacyanido dicobalt(iii) building block for the construction of heterometallic compounds. (10th April 2019) - Alexandru, Maria-Gabriela; Marino, Nadia; Visinescu, Diana; De Munno, Giovanni; Andruh, Marius; Bentama, Abdeslem; Lloret, Francesc; Julve, Miguel
Abstract : The first bimetallic 3d cyanido-bearing complex with 2, 5-dpp as a bridge, (Ph4 P)2 [Co2 III (μ-2, 5-dpp)(CN)8 ]·2H2 O, is obtained and used as a metalloligand with the [Mn(MAC)(H2 O)2 ] 2+ cation to build a Co III Mn II heterobimetallic chain. Abstract : The first bimetallic octacyanido complex of Co III, (PPh4 )2 [Co2 (μ-2, 5-dpp)(CN)8 ] (1 ), was synthesized and used as a metalloligand with [Mn(MAC)(H2 O)2 ]Cl2 ·4H2 O to give a new Co III Mn II heterometallic chain of formula [Mn II (MAC)(μ-NC)2 Co2 III (μ-2, 5-dpp)(CN)6 ] n ·7 n H2 O (2 ) (PPh4 + = tetraphenylphosphonium cation; 2, 5-dpp = 2, 5-bis(2-pyridyl)pyrazine and MAC = 2, 13-dimethyl-3, 6, 9, 12, 18-pentaazabicyclo-[12.3.1]octadeca-1(18), 2, 12, 14, 16-pentaene). Both compounds were characterized by single-crystal X-ray diffraction. Compound1 contains a diamagnetic 2, 5-dpp-bridged dicobalt(iii ) unit with four peripheral cyanide ligands at each cobalt center achieving a six-coordinate surrounding, the electroneutrality being ensured by bulky tetraphenylphosphonium cations. The structure of2 consists of neutral heterobimetallic chains where the [Co2 (μ-2, 5-dpp)(CN)8 ] 2− complex anion adopts a bis-monodentate bridging mode towards the [Mn(MAC)] 2+ cation. Each manganese(ii ) ion in2 is seven-coordinate with five quasi coplanar nitrogen atoms from the macrocycle and two trans -positioned cyanide-nitrogen atoms building a somewhat distorted pentagonal bipyramidal environment. Cryomagnetic measurements for2 reveal the occurrence of quasi magnetically isolated spin sextets in the temperature range of 1.9–300 K.